(untitled) (Vietnam Journal of Community Medicine, 2024)
Introdution: Arteriovenous fistula hemodialysis is an effective solution. The quality of the shut is an important issue and can be seriously affected by complications. High flow is a silent but very dangerous complication, need to evaluate flow characteristics and surgical treatment results. Method: Retrospective, all high-flow AVF patients underwent surgery from 01/2020 to 01/2024 at Thong Nhat hospital. Results and discussion: 36 cases, there are 21 males, 15 females. mean age is 51.3. The mean operating time is 128.8 + 32.6 minutes. Hospitalization is 05.3 + 03.9 days. Shunt closure is 16.7%, Shunt repaired is 83.3%. Arteriovenous flow before surgery (ml/min) 1683.6 + 143.9, after surgery is 757.2 + 182.7, flow decreased statistically significantly (p=0.0041). Heart failure before surgery is 19.4%, after surgery is 13.9%. Surgical complications: infection 05.5%, wound bleeding 11.8%; there were no deaths related to surgery. Conclusion: The prevalence of hypertension in patients with high-flow shunt complications was 77.8%. High-risk arteriovenous fistula complications (>2000ml/min) were 16.6%. Pre and post-operative heart failure was 19.7%, 13.9%, respectively. Surgical repair gave favorable results. Complications were similar to other studies.